Exploring Finnish Student Teachers’ Perceived Coherence of their Teacher Education Program - Mikkilä-Erdmann, Mirjamaija; Nummi, Julia; Erdmann, Norbert (Springer VS, 2025)
Our study investigates how Finnish student teachers experience the coherence of their study program and self-efficacy in teaching. By coherence we mean a continuing process of striving for a consistent teacher education program in which linkages are created between different courses, different stages, as well as theoretical and practical parts of the program. (Canrinus et al., Journal of Curriculum Studies 49:313–333, 2017) In general, the challenge in teacher education is to find the balance between theory and practice during the program. Previous studies have indicated that a lack of coherence may result in fragmented knowledge and skills (e.g., Bain and Moje, Phi Delta Kappan 93:62–65, 2012) and even poor self-efficacy in teaching. The participants of this study are master’s level students from two universities located in southern Finland. They are taking part in either a subject or a classroom teacher education program. Finnish teacher education is a five-year master’s degree program. The teaching practices are integrated in the initial teacher education program. The instrument used in the study is based on previous studies (Canrinus et al., Journal of Curriculum Studies 49:313–333, 2017; Hammerness et al., Coherence and assignments in teacher education: Teacher education survey, University of Oslo Department of Teacher Education and School Research, 2014). In addition, we have included a section about self-efficacy in teaching (Tschannen-Moran and Hoy, Teaching and Teacher Education 17:783–805, 2001). Principle component analysis (N = 127) showed five types of program coherence: opportunity to enact practice, coherence between theory and practice, opportunity to analyze practice, vision of good teaching and self-efficacy. Our results reveal that Finnish student teachers perceive their program as quite coherent and feel prepared for the teacher profession. Minor differences between class and subject teachers were found. Finally, pedagogical conclusions are discussed.
Coherence in European Teacher Education : Theoretical Models, Empirical Studies, Instructional Approaches